CLASSICAL AND NON-CLASSICAL HISTORICISM - Sinjakov, Serhii (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The article explores historicism as a type of worldview and traces its evolution in European and domestic science from the 19th to the early 21st centuries. It investigates the socio-cultural prerequisites and philosophical foundations underlying the transformation and rethinking of the concept of historicism. The place and role of the principle of historicism in shaping the metaphysical foundations of the national idea — understood as a transcendental project reflecting the aspirations and value orientations of the people — are examined. The aim of the research is to identify the mechanisms of formation and transformation of historicism as a significant worldview paradigm in connection with the emergence of new social and information technologies in modern culture. Research methods of the study are historical-philosophical, historical-logical approaches, principles of hermeneutics, cultural-historical and comparative methods. Research results. The postmodern era has rejected classical historicism, significantly altering both conceptual interpretations of it and the methodological approaches to its application in social, historical, and media studies. These changes stem from a transformation in philosophical and historical perspectives on social processes: a revision of the linear concept of time and progress, criticism of teleology and finalist determinism, and skepticism regarding universal laws of social development. All these theoretical changes have directly influenced not only views on history but also the methodologies used to study it. Discussion. An indicative example of postmodern anti-historicism is the formation of views on the "national idea" among different peoples, cultures and civilizations. The policy of "appropriation" of the national idea by a narrow social group, its artificial administrative implantation in the mass consciousness, and the creation of ideological myths — as has repeatedly occurred in history — inevitably lead to a value collapse. There is no national idea that characterizes the nation as a whole; rather, there exist metaphysical projects that should be understood as historical objectifications of the national spirit, which simultaneously constitute its alienation. Conclusions. The development of the concept of historicism, like other cognitive instruments of scientific inquiry, has always occurred within a specific historical context. Political and cultural factors external to science have had a particularly profound impact on social and humanistic knowledge, which is deeply influenced by contemporaneity, worldview, and the values of the era. The evolution of the concept of historicism in the 19th and 20th centuries and in the first quarter of the 21st century clearly exemplifies this interconnection and remains of exceptional relevance today, serving as a vivid illustration of the close relationship between science and society.